2004
DOI: 10.1002/marc.200300105
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Comb‐Like Poly(oxyethylene) and Its Complexes with LiClO4: Synthesis and Mesomorphic Behavior

Abstract: Summary: We prepared an amphiphilic, comb‐like poly(oxyethylene) containing decyl‐tri(oxyethylene) amphiphiles in the side chain using a polymer analogous reaction to obtain a novel nonionic amphiphilic polymeric system with high molecular weight. The amphiphilic comb‐like poly(oxyethylene) itself only showed a side‐chain crystalline phase below its melting temperature of −31 °C. When the polymer was mixed with lithium perchlorate, a smectic liquid‐crystalline phase appeared. The ordered phases of the polymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…7 The number average molecular weight (M n ) and the polydispersity index (M w /M n ) of D3OTP calculated using polystyrene standards by gel permeation chromatography (GPC) were 156,000 g/mol and 1.65, respectively. Theoretically, it is well-known that the comb-like polymer has a more compact hydrodynamic volume compared with that of corresponding linear polymer having identical molecular weight.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 The number average molecular weight (M n ) and the polydispersity index (M w /M n ) of D3OTP calculated using polystyrene standards by gel permeation chromatography (GPC) were 156,000 g/mol and 1.65, respectively. Theoretically, it is well-known that the comb-like polymer has a more compact hydrodynamic volume compared with that of corresponding linear polymer having identical molecular weight.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we found that the hydrophilic core part of D3OTP could be complexed with metallic salt to form thermotropic liquid crystalline phases as mentioned in the introduction part. 7 Similarly, it was also reported that the lyotropic liquid crystalline phases could be obtained from the mixtures of nonionic surfactants that have oligo(oxyethylene) units and transition metal salts through the interactions between the oxyethylene units and the metallic salts. 13,14 We attempted to observe core-shell structures of the D3OTP and Au(III)@D3OTP using atomic force microscopy (AFM) as others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] This provides a useful basis for industrial, pharmaceutical, and biomedical applications. [7][8][9] Since many important therapeutic agents have poor solubility in aqueous solution, it is quite a challenge to develop effective systems for delivery of these agents. Micelle-like aggregates of amphiphilic copolymers have been recently receiving much attention as carriers for hydrophobic drug.…”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic polymers undergo intramolecular microphase separation and form self‐organized aggregates with ordered supramolecular architectures. This provides a useful basis for industrial, pharmaceutical, and biomedical applications 1–3. Recently, amphiphilic saccharide polymers (glycopolymers) have attracted interest in the development of nano‐sized devices, for improving interfacial biocompatibility, and for studying carbohydrate‐protein recognition 4–7.…”
Section: Introductionmentioning
confidence: 99%